Hybrid Amyloid‐Based Redox Hydrogel for Bioelectrocatalytic H2 Oxidation. (26th May 2021) - Duraffourg, Nicolas; Leprince, Maxime; Crouzy, Serge; Hamelin, Olivier; Usson, Yves; Signor, Luca; Cavazza, Christine; Forge, Vincent; Albertin, Luca
Abstract: An artificial amyloid‐based redox hydrogel was designed for mediating electron transfer between a [NiFeSe] hydrogenase and an electrode. Starting from a mutated prion‐forming domain of fungal protein HET‐s, a hybrid redox protein containing a single benzyl methyl viologen moiety was synthesized. This protein was able to self‐assemble into structurally homogenous nanofibrils. Molecular modeling confirmed that the redox groups are aligned along the fibril axis and are tethered to its core by a long, flexible polypeptide chain that allows close encounters between the fibril‐bound oxidized or reduced redox groups. Redox hydrogel films capable of immobilizing the hydrogenase under mild conditions at the surface of carbon electrodes were obtained by a simple pH jump. In this way, bioelectrodes for the electrocatalytic oxidation of H2 were fabricated that afforded catalytic current densities of up to 270 μA cm −2, with an overpotential of 0.33 V, under quiescent conditions at 45 °C. Abstract : A biohybrid prion‐forming domain was synthesized that is capable of undergoing hierarchical self‐assembly into single‐stranded protein nanowires, nanofibers, and supramolecular redox hydrogels. This property enabled us to immobilize a [NiFeSe] hydrogenase within a water‐swollen network of conductive nanofibers by a gentle non‐covalent cross‐linking process while ensuring its wiring to carbon electrodes for electrocatalysis.